Interferometric scattering microscopy (iSCAT): new frontiers in ultrafast and ultrasensitive optical microscopy. - Ortega-Arroyo, J; Kukura, P (2012)
Optical microscopes have for centuries been our window to the microscopic world. The advent of single-molecule optics over the past few decades has ushered in a new era in optical imaging, partly because it has enabled the observation of motion and more recently structure on the nanoscopic scale through the development of super-resolution techniques. The large majority of these studies have relied on the efficient detection of fluorescence as the basis of single-molecule sensitivity. Despite the many advantages of using single emitters as light sources, the intensity and duration of their emission impose fundamental limits on the imaging speed and precision for tracking studies. Here, we discuss the potential of a novel imaging technique based on interferometric scattering (iSCAT) that pushes both the sensitivity and time resolution far beyond what is currently achievable by single-emitter-based approaches. We present recent results that demonstrate single-molecule sensitivity and imaging speeds on the microsecond timescale.